2022
DOI: 10.1155/2022/7002645
|View full text |Cite
|
Sign up to set email alerts
|

Human-Wild Animals Conflict in and around Amba Forest, Ezha District, Gurage Zone, Southern Ethiopia

Abstract: The conflicts between humans and wild animals with the same resources are common but seldom reported in Ethiopia. This study was carried out to assess the causes, impacts, and mitigation strategies of the local communities with human-wild animal conflict (HWC) in and around Amba forest of Ezha District, Gurage Zone, Ethiopia: implications for wildlife conservation. Cross-sectional study design was applied, and data were collected from November 2019 to July 2020 through a semistructured questionnaire, focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Maize (46%, n=79), cassava (46%, n = 79) and groundnut were the most frequently raided cereal crops by olive baboons in the study area. This result is lower than that obtained by [34], whose study was carried out in the Omo valley in southern Ethiopia on the density of wild animal population and their conflict in the Konasa_Pulasa community that showed that the olive baboon was involved in 34.9% of crop raids. This difference would be due to the fact that agriculture in the peripheral villages of the National Parks of Mbam and Djerem is centered on two main crops including cassava and corn unlike that of Ethiopia where farmers cultivate in the same field of corn, beans, potatoes, cotton, millet, sorghum, etc.…”
Section: Discussioncontrasting
confidence: 64%
“…Maize (46%, n=79), cassava (46%, n = 79) and groundnut were the most frequently raided cereal crops by olive baboons in the study area. This result is lower than that obtained by [34], whose study was carried out in the Omo valley in southern Ethiopia on the density of wild animal population and their conflict in the Konasa_Pulasa community that showed that the olive baboon was involved in 34.9% of crop raids. This difference would be due to the fact that agriculture in the peripheral villages of the National Parks of Mbam and Djerem is centered on two main crops including cassava and corn unlike that of Ethiopia where farmers cultivate in the same field of corn, beans, potatoes, cotton, millet, sorghum, etc.…”
Section: Discussioncontrasting
confidence: 64%
“…Human-wildlife con ict is one of the major issues where policymakers and conservationists nd di culties in arriving at lasting solutions. These issues have caused the extinction and decline of several abundant species globally (Sime et al, 2022). HWC has become an essential aspect of conservation these days.…”
Section: Introductionmentioning
confidence: 99%